2018
DOI: 10.1111/ejh.13039
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and cost of pomalidomide in relapsed and refractory multiple myeloma

Abstract: The study demonstrated that pomalidomide-dexamethasone regimen has a long-term favorable safety-efficacy profile in RRMM patients. The survival benefit is substantial even in patients with stable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This has been confirmed in an observational study that described prescribing practices of pomalidomide in a cohort of 63 consecutive MM patients. After a median follow-up of 28 months, 6% of patients had discontinued pomalidomide following severe adverse events, and 38% of patients had required a dose decrease following adverse events [15].…”
Section: Discussionmentioning
confidence: 99%
“…This has been confirmed in an observational study that described prescribing practices of pomalidomide in a cohort of 63 consecutive MM patients. After a median follow-up of 28 months, 6% of patients had discontinued pomalidomide following severe adverse events, and 38% of patients had required a dose decrease following adverse events [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a British series of 39 patients, including one third of DRMM, the ORR was 41%, with a median PFS of 5.2 months, and OS of 13.1 months [17]. Despite the dismal outcome, Sriskandarajah et al suggested that in some patients PomaD could maintain durable response rather than depth response, translating in longer overall survival [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only 21.4% of the patients were able to continue treatment for >1 year. Gueneau et al (16) reported POM effectiveness in the early recurrence phase. However, Palmas et al (17) reported its effectiveness in heavily pretreated patients.…”
Section: Discussionmentioning
confidence: 99%